Design, luminescence properties and applications of Cr3+-doped ScTaO4: a broadband near-infrared phosphor. Issue 42 (12th October 2022) - Wang, Shan; Zhang, Su; Liu, Shuang; Han, Songlin; Li, Xiaodong; Wang, Chaowei; Li, Chengyu
Abstract : A new broadband NIR phosphor, ScTaO4 :Cr 3+, has been synthesized, and the NIR pc-LED devices were prepared. Abstract : Near-infrared (NIR) emitting LED devices have broad applications. Using a visible light LED chip to excite Cr 3+ -activated phosphors to obtain NIR light has attracted extensive attention. In this study, a near-infrared luminescent material, Cr 3+ -doped Sc1− x TaO4, was synthesized by the element substitution method. It demonstrated a long emission wavelength (940 nm) and wide full width at half maximum (FWHM) (186 nm). The morphology, structure and photoluminescence of the samples were investigated using X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and photoluminescence (PL) spectroscopy techniques. Moreover, the relationship between the NIR emission properties of Cr 3+ and the substituted ions in the crystal matrix was studied. Based on this material, we fabricated near-infrared LED devices, which exhibited good near-infrared luminescence properties.